Mild and moderate cardioembolic stroke patients may benefit more from direct mechanical thrombectomy than bridging therapy: A subgroup analysis of a randomized clinical trial (DIRECT-MT) - Cao, Jie; Xing, Pengfei; Zhu, Xucheng; Chen, Ronghua; Shao, Huaming; Xuan, Jinggang; Jiang, Tianwei; Yang, Pengfei; Zhang, Yongwei; Li, Zifu; Chen, Wenhuo; Li, Tianxiao; et al. (Frontiers in Neurology, 2022)
Background The benefit of intravenous alteplase before endovascular thrombectomy is unclear in patients with acute cardioembolic stroke. Methods We collected cardioembolic (CE) stroke patient data from the multicentre randomized clinical trial of Direct Intra-arterial Thrombectomy to Revascularize Acute Ischaemic Stroke Patients with Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals (DIRECT-MT). The primary outcome was the 90-day modified Rankin Scale (mRS) score. Five subgroups of cardioembolic stroke patients were analyzed. A multivariable ordinal logistic regression analysis analyzed the difference in the primary outcome between the direct mechanical thrombectomy (MT) and bridging therapy groups. An interaction term was entered into the model to test for subgroup interaction. The DIRECT-MT trial is registered with clinicaltrials.gov Identifier: NCT03469206. Results A total of 290 CE stroke patients from the DIRECT-MT trial were enrolled in this study: 146 patients in the direct MT group and 144 patients in the bridging therapy group. No difference between the two treatment groups in the primary outcome was found (adjusted common odds ratio, 1.218; 95% confidence interval, 0.806 to 1.841; P = 0.34). In the subgroup analysis, CE stroke patients with an NIHSS ≤ 15 in the direct MT group were associated with better outcomes (47 vs. 53, acOR, 3.14 [1.497, 6.585]) and lower mortality (47 vs. 53, aOR, 0.16 [0.026, 0.986]) than those in the bridging therapy group, while there were no significant differences between the two treatment groups in the outcome and mortality of CE stroke patients with an NIHSS >15. Conclusion Mild and moderate cardioembolic stroke patients may benefit more from direct mechanical thrombectomy than bridging therapy. This need to be confirmed by further prospective studies in a larger number of patients.